Early Gonadal Differentiation, Sex Ratio, and Growth Performance of Nile Tilapia (Oreochromis niloticus) with Tribulus terrestris Extract Supplemen-tation - Sarida, Munti; Lusiani, Lusiani; Putri, Alma Yustika; Elisdiana, Yeni; Adiputra, Yudha Trinoegraha (Department of Aquaculture, 2025)
One way to increase the production of Nile tilapia (Oreochromis niloticus) is to breed dominant male monosex tilapia. Applying natural steroid hormones derived from plants such as Tribulus (Tribulus terrestris) is safe and environmentally friendly. This plant includes flavonoid compounds, steroid saponins, and aphrodisiacs. This study aims to evaluate the effect of Tribulus seed extract on early gonadal differentiation, sex ratio, and growth performance of tilapia juveniles. The study was conducted for 60 days at the Technical Implementation Unit of Freshwater Aquaculture Fisheries Service (UPTD PBAT) in the West Region of Kota Agung, Tanggamus. The study design used was a Completely Randomized Design (CRD) with 5 treatments: 17α-methyltestosterone 0.0005 g/L (P1), and different doses of Tribulus extract 0 g/L (P2); 0.005 g/L (P3), 0.01 g/L (P4), 0.02 g/L (P5) with three replications each. Ten-day-old larvae were immersed in the treatment solutions for 12 hours weekly, repeated three times, and water quality was monitored during the first month to ensure optimal conditions. The larvae were initially fed Artemia four times per day for up to 20 days and then switched to a commercial diet until the end of the rearing period. Histological analysis of gonad sex differentiation was performed at different stages and sampled 10-60 days after hatching to determine the sex ratio of each treatment group. The results showed that the treatment significantly affected the early gonad development and sex ratio (P<0.05), while it did not significantly affect the growth performance and survival rate of tilapia juveniles (P>0.05). The best dose to increase the percentage of males in Nile tilapia was the treatment with Tribulus seed extract at 0.01 g/L.